Philosophy of war - Habiger, Francis Joseph (My University, 1899)
Introduction: This subject was chosen for reasons confronting us at the present time of which at the close of a war, when impulse and emotion are subsided, conscious consideration may better be attained. The steps that we have taken in the late war are either toward imperialism or humanitarianism: either for the better or for the worse. These steps should set us thinking, for, on entering the threshold of a new century, our determination should be stronger than ever, to reason out better the problems before us. Such proposals as the “Czars Manifesto” should be weighed carefully, thought over by every citizen wishing to give a lending hand to progress. The question before us is, “Can war be dispersed with, and if so when and under what circumstances?” But before answering so great a question, it may be well for us to reflect and trace the cause and effect of war, and its substitutes. We may divide war, as Ruskin does into war of play, of dominion, and of defense; but the better way seems to be When treated as evolved from a chronological standpoint of evolution; namely into wars of defense, conquest, religion, political, difficulties, and for humanitarian sentiment.
Citation: Habiger, Francis Joseph. Philosophy of war. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Causes of War; Defense; Conquest; Religion; Political Difficulties; Humanitarian Sentiment; Theses; Manuscripts (documents)